Perilaku dan Pengelolaan Sampah Makanan dari Rumah Tangga, Sektor Komersial, hingga Skala Kota: Tinjauan Pustaka - Lenggo Geni Katlin Jambak; Dhisti Khairunnisa Fahlin; Utama Ladunni Lubis (Jurnal Kendali Teknik dan Sains, 2026)
Food waste is a global environmental issue with wide-ranging impacts on the food supply chain, the burden on final disposal sites (landfills), and greenhouse gas emissions, while the composition of urban waste in Indonesia remains dominated by the organic fraction and its management still relies heavily on landfilling. This literature review examines (1) household-level food waste behavior, covering attitude, norm, meal-planning routine, and socio-demographic factors, as well as city-scale food waste management practices in Singapore, South Korea, Denmark, and Norway; (2) the composition of food waste generated by restaurants, hotels, and street vendors in the City of Bandung; and (3) the effect of composting on methane emission reduction and compost production in the City of Probolinggo through a material flow analysis approach. The synthesis shows that source separation is the primary precondition for successful food waste management at the household, commercial, and city scale alike, although the gap between awareness and actual practice remains a consistent challenge, indicating the need for separated-collection infrastructure, consistent transport chains, and policy incentives to encourage sustainable behavioral change.